2019
DOI: 10.1007/978-3-319-71062-4_16-1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Vegan Food Innovations: A Dual-Market Perspective

Abstract: Veganism is the practice of abstaining from the use of animal products, whether it is for food, clothing, or otherwise. Individuals adhering to veganism are referred to as vegans, and the products they choose to purchase or consume are absent of ingredients sourced from animals.Innovations are products that are appreciated as new and novel by consumers. Vegan food innovations subsequently refer to vegan food products that are seen as new and novel among potential consumers.After their initial introduction to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Over the past few years, the interest in PBD has increased both in the general population and in the scientific community, until it has become one of the main dietary patterns adopted in Western countries. In fact, PBDs have undergone a notable spread thanks to the ever-increasing number of people who have adopted it [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the interest in PBD has increased both in the general population and in the scientific community, until it has become one of the main dietary patterns adopted in Western countries. In fact, PBDs have undergone a notable spread thanks to the ever-increasing number of people who have adopted it [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the increasing interest in vegan diets, there had been a growth in restaurants that only serve plant-based food, which in turn has sparked further curiosity. In addition, According to Dedehayir et al ( 55 ), it is necessary to make dishes that increase curiosity to appeal to more adventurous individuals in major non-vegan markets, and their curiosity induces initial purchases. A study on plant-based food motives among college students in the Midwestern United States found that Fifty-five percent had tried a plant-based alternative to meat.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An increasing number of people are reducing their consumption of animal-based foods or abstaining completely from eating these products [1]. A complete renunciation of animal-based foods is referred to as a plant-based or vegan diet.…”
Section: Introductionmentioning
confidence: 99%